Effect of Prophylactic Calcitriol Administration on Serum Ionized Calcium Concentrations after Parathyroidectomy: 78 Cases (2005–2015) - Armstrong, A.J. (J Vet Intern Med, 2017)
BACKGROUND: Prophylactic administration of calcitriol has been suggested to mitigate the risk of hypocalcemia after parathyroidectomy. The effect of calcitriol on postoperative serum ionized calcium concentrations has not been evaluated in dogs after parathyroidectomy. HYPOTHESIS/OBJECTIVES: To determine the effect of prophylactic calcitriol administration on postoperative serum ionized calcium (iCa) concentrations in dogs with primary hyperthyroidism (PHPTH) treated by parathyroidectomy. ANIMALS: Seventy‐eight dogs with primary hyperparathyroidism treated surgically. METHODS: Multi‐institutional retrospective case study. Medical records from 2005 to 2015 were evaluated. Dogs were included if they had a diagnosis of PHPTH and had surgery to remove parathyroid tissue. Serum iCa concentrations were monitored for a minimum of 2 days postoperatively. Two study groups were evaluated: calcitriol administration and no calcitriol administration. RESULTS: Serial postoperative iCa concentrations measured at 12‐hour time intervals for 2 days postoperatively were positively associated with preoperative iCa concentrations. This association was evident at each time interval, and the effect of preoperative iCa concentrations on postoperative iCa concentrations decreased as time elapsed (12 hours, P < 0.0001; 24 hours, P < 0.0001; 36 hours, P < 0.04; and 48 hours, P = 0.01). Prophylactic calcitriol administration was not found to be significantly associated with postoperative iCa concentrations or its rate of decrease after parathyroidectomy. CONCLUSION AND CLINICAL IMPORTANCE: We found no protective value in administering calcitriol prophylactically to prevent hypocalcemia in the immediate postoperative period (48 hours) after parathyroidectomy. Preoperative iCa concentrations had a significant positive association with postoperative iCa concentrations throughout the monitoring period.